A customer?manufacturer?competitor orientation model for product life cycle analysis based on QFD, AHP/ANP and TRIZ. (11th October 2007) - Hou, Jiachen; Su, Daizhong
With the rapid development of technologies and turbulent market environment, manufacturing industry is challenged with the task of managing products in each stage of Product Life Cycle (PLC). A Customer?Manufacturer?Competitor (CMC) model is developed, which helps manufacturers to analyse customer's, competitor's and manufacturer's orientation and related issues within the PLC. The CMC model consists of three evaluation processes, namely, customer-based evaluation, manufacturer-based evaluation and ideal formulation. In this paper, the characteristics of PLC and the six evaluation sets for assessing the performance of a manufacturer and its competitors in each PLC stage are presented; the advantages of integrating Quality Function Deployment (QFD), Theory of Inventive Problem Solving (TRIZ) and Analytical Hierarchy Process/Analytical Network Process (AHP/ANP) into the CMC model are discussed and then the CMC model is described, followed by a case study illustrating how the CMC model can be applied in the PLC analysis.